Dementia and Hip Fractures: Development of a Pathogenic Framework for Understanding and Studying Risk - Friedman, Susan M. (SAGE Publications, 2010)
Dementia and hip fractures are 2 conditions that are seen primarily in older adults, and both are associated with substantial morbidity and mortality. An individual with dementia is up to 3 times more likely than a cognitively intact older adult to sustain a hip fracture. This may occur via several mechanisms, including (1) risk factors that are common to both outcomes; (2) the presence of dementia increasing hip fracture incidence via intermediate risk factors, such as falls, osteoporosis, and vitamin D; and (3) treatment of dementia causing side effects that increase hip fracture risk. We describe a model that applies these 3 mechanisms to explain the relationship between dementia and hip fractures. Comprehensive understanding of these pathways and their relative influence on the outcome of hip fracture will guide the development of effective interventions and potentially improve prevention efforts.